Research progress and application of the CRISPR/Cas9 gene-editing technology based on hepatocellular carcinoma - Shijing Yu; Ruirui Zhao; Bingchen Zhang; Chunmei Lai; Linyan Li; Jiangwen Shen; Xiarong Tan; Jingwei Shao (Elsevier, 2023)
Hepatocellular carcinoma (HCC) is now a common cause of cancer death, with no obvious change in patient survival over the past few years. Although the traditional therapeutic modalities for HCC patients mainly involved in surgery, chemotherapy, and radiotherapy, which have achieved admirable achievements, challenges are still existed, such as drug resistance and toxicity. The emerging gene therapy of clustered regularly interspaced short palindromic repeat/CRISPR-associated nuclease 9-based (CRISPR/Cas9), as an alternative to traditional treatment methods, has attracted considerable attention for eradicating resistant malignant tumors and regulating multiple crucial events of target gene-editing. Recently, advances in CRISPR/Cas9-based anti-drugs are presented at the intersection of science, such as chemistry, materials science, tumor biology, and genetics. In this review, the principle as well as statues of CRISPR/Cas9 technique were introduced first to show its feasibility. Additionally, the emphasis was placed on the applications of CRISPR/Cas9 technology in therapeutic HCC. Further, a broad overview of non-viral delivery systems for the CRISPR/Cas9-based anti-drugs in HCC treatment was summarized to delineate their design, action mechanisms, and anticancer applications. Finally, the limitations and prospects of current studies were also discussed, and we hope to provide comprehensively theoretical basis for the designing of anti-drugs.